PENGARUH MEDIA KARTU ANGKA TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN 1-10 KELOMPOK A DI TK KATOLIK SANTA THERESIA KALIJUDAN SURABAYA - Geri Fransiska; Nurul Khotimah (LPPM Universitas Negeri Surabaya, 2023)
The ability to recognize number symbols is one of the abilities that early childhood needs to possess. the ability to recognize number symbols can be improved through learning media, one of which is using number card media. Number card media used in number symbol recognition activities. This study aims to describe and see the influence of number card media on the ability to recognize number symbols in children aged 4-5 years. The type of research used is a quantitative descriptive survey with a technique that accommodates data through distribution via google forms. The analysis technique uses descriptive qualitative. Based on result of the calculation of the survey data, 66% of the 30 respondents indicated that number card media is suitable for use as a medium to improve the ability to recognize number symbols in children aged 4-5 years. Based on data processing, it can be concluded that number card media can stimulate the ability to recognize number symbols 1-10 in children aged 4-5 years. Keywords: Number Cards, Number Symbols, Early Childhood